Criteria for Models of Tertiary Education Ventures in Malaysia - Chiang, Jeffrey C.L; Cheng, Sheila (2019)
In the past few decades of nation development, Malaysia has seen the tertiary education system being revolutionalised from having a handful of public universities to expand into hundreds of private universities and colleges, operating side by side with the wellestablished public universities. Although the public and private universities, coined as institutions of higher learning (IHLs), have different models of operation and financial management, the focus of this paper is on the how to select criteria for best business models to establish and to run a private university or college in Malaysia. The most common model found among all viable models is one that has an established relationship with either a local or foreign institution. The objective of this study is to explore alternate viable education business start-ups which can contribute to the rapid development of Malaysia as an education hub which not only attracts local students but also the international students. This study adopts a qualitative approach with a focus on multiple causes, which are Universiti Tunku Abdul Rahman, Monash University Sunway and Taylors University. The selected cases shared a common feature in their business model which is sustainable and exist for several decades. The preliminary findings show that those business model ventures which mirror established institutions stand to gain as a successful start-up, whereas the unorthodox models used tend to be more flexible, lean and able to face and adapt to changing circumstances in the market swings in education demands